STUDI POTENSI WISATA CAGAR BUDAYA DESA SANGLIAT DOL - Edoardus Edwyn Ayowembun; Suryono Herlambang; Jo Santoso (Jurusan Arsitektur dan Perencanaan, 2021)
Sangliat Dol Village is one of the tourist villages located in Wertamrian sub-district, Tanimbar Islands Regency with an area of 20 hectares. Sangliat Dol Village is a tourist village area contained in the Tourism Area Development Plan in the Tanimbar Islands Regency and is written in the RTRW of West Southeast Maluku Regency 2012-2032 as a Cultural Tourism Area. The Cultural Tourism Area was developed in several villages, as an old traditional village that still has an important role in the cultural structure of West Southeast Maluku Regency. Sangliat Dol Village is also designated as the National Tourism Development Area (KPPN) of Tanimbar. However, the potential and attraction possessed by Sangliat Dol Village in the form of natural scenery, customs that are still closely attached, and historical relics have not been utilized to the maximum so that if developed properly it can increase the interest of domestic and foreign tourists to come to visit the village. Sangliat Dol. The author conducts several analyzes such as analysis of determining cultural heritage, location analysis, area footprint analysis, best practice analysis and analysis of proposed approaches to developing cultural heritage tourism so as to produce proposals for the concept of developing the Sangliat Dol Village Tourism Area in order to achieve a sustainable cultural heritage tourism area and attract tourists . Keywords: Cultural Conservation; Tourism; Customs; Ecotourism approach.Abstrak Desa Sangliat Dol merupakan salah satu desa wisata yang terletak di kecamatan Wertamrian, Kabupaten Kepulauan Tanimbar dengan luas wilyah 20 Ha. Desa Sangliat Dol merupakan wilayah desa wisata yang terdapat dalam Rencana Pengembangan Kawasan pariwisata di wilayah Kabupaten Kepulauan Tanimbar serta tertulis dalam RTRW Kabupaten Maluku Tenggara Barat 2012-2032 sebagai Kawasan Wisata Budaya. Kawasan Wisata Budaya dikembangkan dibeberapa desa, sebagai desa adat tua yang masih memiliki peran penting dalam struktur budaya Kabupaten Maluku Tenggara Barat. Desa Sangliat Dol juga ditetapkan sebagai Kawasan Pengembangan Pariwisata Nasional (KPPN) Tanimbar. Namun potensi dan daya Tarik yang dimiliki oleh Desa Sangliat Dol berupa pemandangan alam, adat istiadat yang masih melekat erat, serta peninggalan – peninggalan sejarah ini belum dimanfaatkan dengan maksimal sehingga jika dikembangkan dengan baik dapat meningkatkan minat wisatawan domestik maupun wisatawan mancanegara untuk datang berkunjung ke Desa Sangliat Dol. Penulis melakukan beberapa analisis seperti analisis penentuan cagar budaya, analisis lokasi, analisis tapak kawasan, analisis best practice serta analisis usulan pendekatan pengembangan wisata cagar budaya sehingga menghasilkan usulan untuk konsep pengembangan Kawasan Wisata Desa Sangliat Dol demi tercapainya Kawasan wisata Cagar budaya yang berkelanjutan dan diminati wisatawan.